The influence of perceived usefulness, perceived ease of use, perceived risk on behavioral intention for QRIS user - Muhammad Yusuf; Rahmiati, Rahmiati; Thamrin, Thamrin (Marketing Management Studies, 2024)
The purpose of this study is to analyze: (1) the effect of perceived usefulness on behavioral intention (2) the effect of perceived ease of use on perceived usefulness (3) the effect of perceived ease of use on behavioral intention (4) the effect of perceived risk on behavioral intention for QRIS in Padang. We did this by asking 310 QRIS users in Padang for their opinions. We collected our data directly from these users, who were interested in QRIS payments. Then we used a mix of descriptive and quantitative analysis, including multiple regression, to analyze the data using SmartPLS. The results of the study showed: perceived usefulness and perceived ease of use had a positive significant effect on behavioral intention; perceived ease of use had a positive significant effect perceived usefulness; perceived risk had a negative significant effect on behavioral intention.